2015
DOI: 10.1016/j.cell.2015.10.074
|View full text |Cite
|
Sign up to set email alerts
|

Descending Command Neurons in the Brainstem that Halt Locomotion

Abstract: SUMMARY The episodic nature of locomotion is thought to be controlled by descending inputs from the brainstem. Most studies have largely attributed this control to initiating excitatory signals, but little is known about putative commands that may specifically determine locomotor offset. To link identifiable brainstem populations to a potential locomotor stop signal, we used developmental genetics and considered a discrete neuronal population in the reticular formation: the V2a neurons. We find that those neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
312
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(344 citation statements)
references
References 59 publications
(99 reference statements)
16
312
3
Order By: Relevance
“…Importantly, elevated firing rates precede movement indicating that NGC provides the basis for sensory responsivity. Lastly, recent studies (Bretzner and Brownstone, 2013; Bouvier et al, 2015) showed that medullary reticular glutamatergic neurons are centrally involved in the activation of movement. Thus, these functional and anatomical features suggest that NGC is a strategic location for promoting arousal.…”
Section: Molecular Regulation Of Gamentioning
confidence: 99%
“…Importantly, elevated firing rates precede movement indicating that NGC provides the basis for sensory responsivity. Lastly, recent studies (Bretzner and Brownstone, 2013; Bouvier et al, 2015) showed that medullary reticular glutamatergic neurons are centrally involved in the activation of movement. Thus, these functional and anatomical features suggest that NGC is a strategic location for promoting arousal.…”
Section: Molecular Regulation Of Gamentioning
confidence: 99%
“…Thus, future quests probing the molecular heterogeneity of the mesencephalic locomotor region and medulla nuclei might unravel more dedicated pathways recruited in a context-dependent manner. Finally, another more restricted glutamatergic subpopulation (Chx10 + ) in the medulla has been described as necessary to halt locomotion [14], and understanding if and how this subpopulation is recruited by the mesencephalic locomotor region–lateral paragigantocellular nucleus pathway and whether it acts in conjunction with the pedunculopontine nucleus to promote a stop and explore behavior would shed further light on the logic of descending motor control.…”
Section: Discussionmentioning
confidence: 99%
“…The marker is non-specific for NGC neurons; it also labels neurons elsewhere. More importantly, Chx10 labeled (V2a) brainstem neurons exert inhibitory influence on locomotion [67], a function opposite of that expected of neurons involved in arousal. Since we intended to study large NGC neurons that may regulate arousal, neurons with Chx10 marker are of little use.…”
Section: Discussionmentioning
confidence: 99%